Impact of exotic Ponderosa pine (Pinus ponderosa Doug. ex Laws.) plantations on water resources in northwestern Patagonia, Argentina - Licata, Julián Andrés (Oregon State University, 2020)
Tesis para obtener el grado de Doctor of Philosophy (Ph.D.), de la Oregon State University, en diciembre de 2007